Endoscopic Retroperitoneal Adrenalectomy for Adrenal Metastases. (7th September 2014) - Simutis, Gintaras; Lengvenis, Givi; Beiša, Virgilijus; Strupas, Kęstutis
Abstract : Objectives . To evaluate whether retroperitoneal approach for adrenalectomy is a safe and effective treatment for adrenal metastases (AM). Methods . From June 2004 to January 2014, nine consecutive patients with AM were treated with endoscopic retroperitoneal adrenalectomy (ERA). A retrospective study was conducted, and clinical data, tumor characteristics, and oncologic outcomes were acquired and analyzed. Results . Renal cancer was the primary site of malignancy in 44.4% of cases. The mean operative time was 132 ± 10.4 min. There were 5 synchronous and 4 metachronous AM. One patient required conversion to transperitoneal laparoscopic procedure. No mortality or perioperative complications were observed. The median overall survival was 11 months (range: 2–42 months). Survival rates of 50% and 25% were identified at 1 and 3 years, respectively. At the end of the study, 4 patients were alive with a mean observed follow-up of 20 months. No patients presented with local tumor relapse or port-site metastases. Conclusions . This study shows that ERA is a safe and effective procedure for resection of AM and advances the surgical treatment of adrenal disease. The use of the retroperitoneal approach for adrenal tumors less than 6 cm can provide very favorable surgical outcomes.